Identifikasi Eschericia coli dan Salmonella sp. pada Air Kolam Renang Candi Pari: Identification of Eschericia coli and Salmonella sp. on the Pari Temple Swimming Pool Water - Khakim, Lukmanul; Rini, Chylen Setiyo (Universitas Muhammadiyah Sidoarjo, 2018)
Incorrect treatment of swimming pool can contaminate the water with bacteria. Common bacteria in water are Escherichia coli and Salmonella sp, both of which may infect the users of the swimming pool. Infection causes diarrhea and high fever on humans. The aim of this research is to investigate the contamination of Escherichia coli and Salmonella sp at Candi pari swimming pool. Research design used in this research is the development of EMB and SSA selective medium, gram coloring test, and biochemical test to confirm the presence of Escherichia coli and Salmonella sp. Resultsfrom this research is the growth of Escherichia coli and Salmonella sp from 1 ml sample which were inoculated on selective medium. Conclusion from this research is from 2 samples taken from Candi Pari swimming pool, both are positively contaminated with Escherichia coli and Salmonella sp.